The Successes of Community Benefits Agreements - Olatoye, Francis; Ong, Frank; Pavalagantharajah, Sureka; Ulgenald, Ilayda; Yang, Hunster (Prepared by the McMaster Research Shop for the Hamilton Community Benefits Network, 2019)
Community benefits are becoming increasingly popular in Ontario, particularly with the use of strategic tools like Community Benefits Agreements (CBAs). CBAs are used to ensure that affected residents will share in the benefits of major development projects. The purpose of this report is to provide the Hamilton Community Benefits Network with a review and analysis of various case studies that have used CBAs. Specifically, CBAs in the United States and Canada have revealed various successes of CBAs in terms of outputs, results, and benefits achieved. Based on the findings, the report also provides recommendations for CBA best practices. In particular, recommendations for the City of Hamilton have been proposed, which includes the development of a formal, municipal-wide CBA Policy.
Keywords: Hamilton, community-based research, community benefits, community benefits agreements